Phenotypic differences in the appearance of soft rice and its endosperm structural basis - Fan, Peng; Xu, Jian; Wang, Zhijie; Liu, Guodong; Zhang, Zhenzhen; Tian, Jinyu; Wei, Haiyan; Zhang, Hongcheng (Frontiers in Plant Science, 2023)
In order to clarify endosperm structures and the resulting differences in appearance phenotypes between different soft rice genotypes, four soft rice varieties were selected in this study, including two varieties with good-appearing and two varieties with cloudy appearance. The differences in appearance phenotypes and endosperm structure in mature grains of soft rice with different appearance phenotypes were scientifically analyzed, and the development process of their endosperm differences at the filling stage was investigated. The results show that the difference in the rice appearance of different soft rice varieties mainly lay in the basic transparency and chalkiness. These differences in rice appearance were caused by two completely different types of endosperm structure. Fewer and smaller starch pores were responsible for higher basic transparency of soft rice, denser starch granules arrangement caused the lower chalkiness of the soft rice grains. At ten days after flowering, the starch granules in the back and heart of the good-appearing soft rice were already significantly fuller and more closely packed than those of the cloudy soft rice, while the number and area of starch granule holes were significantly smaller than those of the cloudy soft rice. This difference was gradually increasing until maturity. From the perspective of appearance evaluation, soft rice with good-appearing should have both high basic transparency and low chalkiness. The endosperm starch granules should be full and tightly arranged, and the number of starch pores should be small and the area should be small. During the filling period, reasonable cultivation measures should be taken to promote the development of a high-quality appearance of soft rice.